Progressive Muscle Relaxation Reduces Blood Pressure in Older Adults with Hypertension - Anggraini, Ria; Poppy Farasari; Triana Maharani (Future Science, 2024)
Introduction: The physiological aging process in older adults may lead to various disturbances in the cardiovascular system, including hypertension. One approach to controlling blood pressure is through progressive muscle relaxation therapy. This study aimed to investigate the effect of progressive muscle relaxation on blood pressure in older adults with hypertension at the Social Service Unit for Older Adults in Blitar and Nursing Home in Tulungagung in 2023. Methods: This study employed a quasi-experimental method with a one-group pre-post test design. The population consisted of all older adults with hypertension at the research site in 2023, totaling 80 individuals. Purposive sampling was used to recruit the samples of 39 participants. Observation sheets and a sphygmomanometer were utilized for data collection. Result: The results showed that before receiving progressive muscle relaxation therapy, most participants had stage-1 hypertension, with 23 participants (59%), and stage-2 hypertension, with 16 participants (41%). After the therapy, the majority of participants were included in the stage-1 hypertension category, with 26 participants (67%), and prehypertension, with 5 participants (13%). The Wilcoxon test showed a significant value of ρ = 0.000 < α = (0.05), indicating the effect of progressive muscle relaxation therapy on blood pressure. This means that regular therapy sessions may lead to better blood pressure control in hypertensive patients. Conclusion: Progressive muscle relaxation therapy can increase endorphin hormone production and reduce stress levels, thereby stabilizing blood pressure.